The Relationship Between Visual Components and the Perceived Restorative Quality of Green Open Spaces : (Case Study: Lapangan Banteng, Jakarta) - Robiadji, Chiara; Ernawati, Jenny; Santosa, Herry (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2026)
Green open spaces (GOS) in Jakarta play a vital role in supporting the psychological well-being of its users, but not much is known about whether the design of GOS is related to users’ perception of its restorative quality. To broaden such knowledge, this study aims to explore the relationship between visual components in GOS and its perceived restorative quality while using Lapangan Banteng as a case study. A survey research method was applied, in which a structured questionnaire is employed to gather park users’ perceptions of its visual components and restorative quality. Relationships between variables are then explored using correlation analysis, which revealed that several visual components, such as vegetation density, pavement patterns, and natural materials in Lapangan Banteng, had strong to moderate and statistically significant correlations across multiple dimensions of perceived restorative quality. The results indicated that certain visual components could potentially bring positive contributions to its users’ psychological well-being, but further research is needed to test whether those relationships are positively or negatively related.